Symmetry Group Analysis of a Fifth-Order KdV Equation with Variable Coefficients. Issue 4 (6th June 2016) - de la Rosa, R.; Gandarias, M. L.; Bruzón, M. S.
ABSTRACT: Symmetry group analysis is carried out on a generalized fifth-order KdV (foKdV) equation involving many arbitrary functions. Equivalence transformations group has been determined. This allows us to perform a comprehensive study by reducing the equation to a subclass with fewer number of arbitrary elements. Furthermore, we have established the subclasses of the reduced equation which are nonlinearly self-adjoint. The property of nonlinearly self-adjointness is used to construct conserved vectors from the classical symmetries of the equation by using a general theorem on conservation laws. We also determine conservation laws by using the multipliers method.